Early portal vein thrombosis after pediatric liver transplantation: Assesment of risk factors (Annals of Medical Research, 2023)
Aim: Despite advancements in surgical techniques, early portal vein thrombosis (ePVT) continues to be one of the major complications of liver transplantation (LT) in pediatric age group. Possible risk factors are portal vein diameter < 5 mm, infancy, patient body weight < 10 kg and high graft recipient weight ratios (GRWR > 4.0). We retrospectively evaluated our records of pediatric LTs’ in terms of ePVT and possible risk factors determining development of this dreaded complication.Materials and Methods: Between January 2018 and January 2022, 228 LTs were performed for pediatric age (under the age of 18) group at Inonu University, Liver Transplantation Institute. Among these patients, 212 were eligible for the study. Patients with ePVT were defined as Portal Vein Thrombüs Group  (PVTG) and patients with no Portal Vein thrombosis were defined in control group (CG). ePVT was described as detection of impeded portal venous outflow with imaging studies either perioperatively or within postoperative 3 days . Demographic, clinical and operative variables were retrospectively evaluated.Results:  Among 212 LTs, 24 cases were complicated with ePVTs (11.3 %). Preoperative platelet counts, etiology of Budd-Chiari, postoperative hepatic artery thrombosis (HAT) and lower age were significantly higher for early PVT. In multivariate analysis, preoperative platelet levels, etiology of Budd-Chiari and postoperative HAT were significantly higher for PVT. One and 5 years overall survivals (OS) for PVTG and CG were 50.0 % - 50.0 % and  69 % - 63 % respectively. No significant OS difference was observed despite much more patients were died in PVTG.Conclusion: High preoperative platelet counts, Budd-Chiari syndrome and postoperative HAT are predictive factors for ePVT. Anti-thrombotic prophylaxes can be considered in high-risk patients. Venous jump grafts seem to have no effect on ePVT. Despite PVT increases the mortality rates, it can be resolved easily with immediate reoperation.
Keywords: Pediatric liver transplantation; Portal vein; Thrombosis